PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MACROMEDIA FLASH PADA KOMPETENSI MENGOPERASIKAN MESIN FRAIS MELALUI PEMBELAJARAN LANGSUNG UNTUK SISWA KELAS XI SMK PROGRAM STUDI TEKNIK MESIN - Yuwono, Tri; Cholik, Mochamad; munoto, munoto (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
Abstract Operating milling machine is one of the standard competences which must be mastered by the studens of mechanical engineering in vocational hight school. One of the ways to help students comprehend the learning materials of milling machine operating is by using appropriate and effective learning set. Therefore, this research develops macromedia flash based learning set in the milling machine operating through direct learning especiallyin making the straight cut gears which aims to make the students be able to pass the students? study result. This learning set are developed by adapting 4-D model. There are define, design, develop, and disseminate. The data collecting techniques used are expert validation, observation , test and students? questionnaire. The subjectsof the research are the students of eleventh grade at mechanical engineering department of SMK Negeri 2 Wonosari. The researchis designed by using one group pretest-posttest design. The data is collected by giving pretest, applying the developed learning sets, and giving the posttest. The research data is analyzed by using descriptive statistic analysis technique. The result of the research finds that : 1) the learning set which is developed in the form of syllabus, lesson plan, students? work sheet, learning media, and scoring sheetis very valid and its average score is 3.5, 2) the lesson plan is well implemented and its average score is 4.4, 3) the students? activity in the learning process is very active and its average score is 3.2, 4) the students? response for the learning is very positive for 88%, 5) the students?study result can be achieved well either individually or classically. To sum up, the macromedie flash based learning set for milling machine operating through direct learning for the straight cut gears has been developed well and is effective to make the student be able to pass their study. Keywords: direct learning, Macromedia flash